I. Costanzo, S. Murgia, G. Valenti, F. Fasani. Experimental investigation on a sliding-vane expander for steam applications / trans. from Engl. M. A. Fedorova - M. A. Fedorova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
There are many industrial plants that use steam as an energy vector at different pressure levels, in which pressure reduction is commonly performed by a throttling valve, resulting a totally irreversible process. It is possible to recover this energy through an expander that generates mechanical or electric energy. This work is focused on the analysis of a highly innovative steam expander based on sliding-vane technology. The design principles of the sliding-vane expander and two experimental campaigns are presented. The first experimental campaign allows to assess the reliability of the system with steam as working fluid, the second campaign leads to assess the stability during long-run and the performance of the system. A maximum expander mechanical power of 28 kW is measured. The pressure-volume diagram of the expansion process is also measured and presented.